Surface treatment method for improving corrosion resistance of 8Cr4Mo4V steel bearing
Through the composite processing process of plasma ion implantation and magnetron sputtering deposition, a multiphase composite layer with a nano-modulated structure is formed, which solves the problem of poor corrosion resistance of 8Cr4Mo4V steel bearing steel, and significantly improves the corrosion resistance and wear resistance of the bearing.
Patent Information
- Application Number
- CN202411762023.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-04
AI Technical Summary
The existing 8Cr4Mo4V steel bearing steel has poor corrosion resistance, and the traditional surface treatment process shows limitations under high load and complex working conditions, such as insufficient coating bonding and limited corrosion resistance improvement.
The plasma ion implantation and magnetron sputtering deposition composite treatment process is adopted, and nitrogen ion implantation and magnetron sputtering deposition chromium layer are alternately carried out to form a multi-phase composite layer with a nano-modulated structure to improve the corrosion resistance and wear resistance of the bearing.
The corrosion resistance and wear resistance of 8Cr4Mo4V steel bearings are significantly improved, the bonding force between the chromium layer and the substrate is enhanced, and the service life of the bearing is extended.
Smart Images

Figure CN119553240A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal surface treatment and modification, and specifically relates to a surface treatment method for improving the corrosion resistance of an 8Cr4Mo4V steel bearing through a composite treatment process of plasma ion implantation and magnetron sputtering deposition. Background Art
[0002] Bearing steel is widely used in aerospace engines, automobiles and industrial fields due to its demand for high strength, wear resistance and corrosion resistance under extreme working conditions. Traditional surface treatment processes, such as nitriding, carburizing, and single-layer coatings (such as chromium nitride coatings) deposited by magnetron sputtering, can improve the surface corrosion resistance of bearing steel, but they still show obvious limitations under high loads and complex working conditions. For example, nitriding and carburizing processes have limited improvement in corrosion resistance; single-layer chromium nitride coatings have achieved good corrosion resistance through magnetron sputtering deposition technology, but the coating has limited bonding strength and is easy to peel off under high loads or cyclic loads, and microcracks and pores may lead to the penetration of corrosive media, thereby weakening the protective effect. In order to solve these problems, many advanced surface treatment technologies have gradually been applied, such as magnetron sputtering deposition of multilayer films, ion implantation and laser surface alloying. However, these technologies still have shortcomings in practical applications: although magnetron sputtering deposition of multilayer films can enhance corrosion resistance through multilayer structures, the interfacial bonding between the coatings is weak and may cause delamination or peeling under cyclic loads; ion implantation can improve surface corrosion resistance by introducing corrosion-resistant elements, but due to the shallow treatment depth, it is easy to wear and fail after long-term operation; laser surface alloying can form a corrosion-resistant fusion layer, but the stress concentration caused by rapid cooling can easily cause crack propagation. For bearings, surface wear resistance is an important technical indicator. While improving corrosion resistance, the surface hardness should not be reduced. Therefore, there is an urgent need for methods that can meet the requirements of corrosion resistance while maintaining or even improving surface wear resistance. Current research shows that the combined application of magnetron sputtering deposition and ion implantation technology to form an ion implantation hybrid film can not only significantly improve the corrosion resistance of bearing steel, but also improve its surface wear resistance, which can meet the long-term use requirements of harsh working conditions. Summary of the invention
[0003] The purpose of the present invention is to solve the problems that the existing 8Cr4Mo4V steel bearing steel has poor corrosion resistance, other surface treatment processes have poor bonding strength and limited corrosion resistance improvement, and to provide a surface treatment method that can not only improve the corrosion resistance of 8Cr4Mo4V steel bearings, but also is beneficial to surface wear resistance.
[0004] The surface treatment method for improving the corrosion resistance of 8Cr4Mo4V steel bearings of the present invention is implemented according to the following steps:
[0005] 1. Sample surface cleaning:
[0006] The 8Cr4Mo4V steel bearing parts are placed in a cleaning solution for ultrasonic cleaning to remove surface oil and contaminants to obtain cleaned bearing parts;
[0007] 2. Argon ion etching treatment:
[0008] Put the cleaned bearing parts into the workstation in the vacuum chamber and evacuate the vacuum chamber. When the back vacuum is less than 1×10 -3 After the pressure reaches 1-10 Pa, argon working gas is introduced, and the pressure reaches 1-10 Pa. The argon gas is excited by radio frequency to form plasma, and a negative bias voltage is applied to the bearing parts to perform ion bombardment cleaning, thereby obtaining the bearing parts after ion cleaning.
[0009] 3. Initial nitrogen ion implantation:
[0010] In a plasma ion implanter equipped with a magnetron sputtering target, nitrogen is used as the working gas, the working gas pressure in the vacuum chamber is adjusted to 0.1-1 Pa, radio frequency is used to excite nitrogen to form plasma, and the bearing parts after ion cleaning are subjected to nitrogen plasma ion implantation treatment to form a pretreatment layer, thereby obtaining bearing parts subjected to pre-nitrogen ion implantation treatment;
[0011] 4. Magnetron sputtering deposition of chromium layer:
[0012] The working gas pressure in the vacuum chamber is adjusted to 0.1-5 Pa, argon gas is used as the working gas, and a pure chromium target is used to deposit a chromium layer on the bearing parts pre-treated by nitrogen ion implantation by magnetron sputtering for 0.5-5 hours, so as to deposit a chromium layer on the surface of the bearing parts;
[0013] 5. Plasma ion implantation of nitrogen:
[0014] The working gas pressure in the vacuum chamber is adjusted to 0.1-1 Pa again, nitrogen is switched as the working gas, radio frequency is used to excite nitrogen to form plasma, and nitrogen plasma ion implantation is performed on the bearing parts. The acceleration voltage is controlled to 10-50 kV to form a nitrogen-chromium atomic mixed layer on the surface of the bearing parts.
[0015] 6. Cyclic magnetron sputtering deposition of chromium and nitrogen ion implantation:
[0016] Repeat the magnetron sputtering deposition of the chromium layer in step 4 and the nitrogen plasma ion implantation in step 5 for many times to form a multi-layer nitrogen-chromium atomic mixed layer of a certain thickness on the surface of the bearing parts, thereby completing the surface treatment method for improving the corrosion resistance of 8Cr4Mo4V steel bearings.
[0017] The surface treatment method for improving the corrosion resistance of 8Cr4Mo4V steel bearings of the present invention, in the process of nitrogen ion implantation into the chromium layer in step 5, when high-energy nitrogen ions enter the chromium layer, they obtain electrons and become nitrogen atoms, which collide, scatter, dissolve and react with chromium atoms, and nitrogen dissolves in the steel or generates hard nano-level chromium nitride and dichromium nitride, thereby improving the hardness of the chromium layer and enhancing the corrosion resistance and wear resistance. The implantation of nitrogen ions will generate residual compressive stress in the chromium layer, and this compressive stress can inhibit the expansion of cracks and improve the hardness of the film.
[0018] By adjusting the time of chromium deposition, as well as adjusting the energy and time of ion implantation, an ion implantation mixed layer with different chromium-nitrogen atomic ratios can be formed. Since the concentration distribution of the ion implantation layer is a quasi-Gaussian distribution, the nitrogen concentration in the mixed layer is not uniform. In this way, a multi-period alternating film structure is formed on the bearing surface after multiple cycles. The ion implantation energy determines that the depth of each implantation is tens of nanometers, and the total thickness of the film layer can reach the micrometer level according to the number of cycles. Finally, multiple depositions and injections form a thin film of a nano-modulation structure, and the matrix component chromium of the nano-structure modulation layer is continuous, and the nitride phase changes periodically with the change of the cycle period. Conventional single-layer multiphase deposition processes may require the use of a multi-target system or frequent replacement of targets to achieve the layering of different materials. In the surface treatment method of the present invention, a composite structure containing chromium, chromium nitride and dichromium nitride can be directly deposited on the chromium layer by multi-cycle nitrogen ion implantation, which not only simplifies the operation, but also reduces the equipment preparation and adjustment time, and improves the operating efficiency. In addition, the consistency of this process step also reduces the risk of cross contamination in the production process, making the processing process more controllable. Nitrogen ion implantation penetrates the chromium layer to the substrate surface, improving the bonding force between the chromium layer and the substrate. Compared with a single-layer deposited pure phase material, this surface treatment method introduces an additional bonding enhancement layer at the interface. The composition and content of the multiphase nano-scale composite structure phase can be controlled by controlling the process parameters, thereby improving the comprehensive mechanical properties of the film. Compared with a single-layer pure phase material, the mutual cooperation between the nanophases of the composite structure shows higher durability during friction and wear; the nano-composite structure can also disperse external stress and reduce the generation and expansion of cracks. The most important thing is that the multiphase composite layer of chromium, chromium nitride and dichromium nitride is more complex than a single pure phase layer, especially at the nanoscale, and this complexity has a significant impact on the invasion path of the corrosive medium. The grain boundaries, phase boundaries and nano-sized microstructures in the multiphase structure can form a complex diffusion path, so that the corrosive medium must pass through multiple barrier layers when penetrating, which prolongs the time for the corrosive medium to reach the substrate. Compared with a single chromium layer or chromium nitride layer, this multiple barrier can significantly reduce the medium penetration rate, thereby enhancing the corrosion resistance of the bearing.
[0019] The present invention alternately deposits chromium by magnetron sputtering and ion implants nitrogen, so that a transition layer with high bonding force is formed between the film layer and the substrate, a multi-phase composite layer with a nano-modulated structure is generated on the surface, and the interfaces between the film layers formed by multiple depositions are not obvious due to the mixing effect of ion implantation. This method significantly improves the corrosion resistance of the bearing, and also improves the surface hardness and wear resistance of the bearing.
[0020] The present invention adopts plasma ion implantation technology and cooperates with a magnetron sputtering system equipped in the same vacuum chamber to meet the requirements of preparing corrosion-resistant films on the surfaces of bearings with complex structures. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A schematic diagram of the process principle of the surface treatment method for improving the corrosion resistance of 8Cr4Mo4V steel bearings according to the present invention;
[0022] Figure 2 This is a transmission electron microscope (TEM) high-resolution dark field image of the coating obtained after the surface treatment of the bearing steel workpiece in the embodiment;
[0023] Figure 3 Surface scanning diagram of nitrogen, chromium and iron elements in the coating obtained after the surface treatment of the bearing steel workpiece in the embodiment;
[0024] Figure 4 The X-ray diffraction (XRD) analysis diagram of the coating obtained after the surface treatment of the bearing steel workpiece in the embodiment;
[0025] Figure 5 This is a nano-hardness test diagram of a bearing steel workpiece after surface treatment in the embodiment;
[0026] Figure 6 This is a photo of the bearing steel workpiece after 96 hours of neutral salt spray test in the embodiment;
[0027] Figure 7 This is a scanning electron microscope (SEM) morphology image of a bearing steel workpiece after a 96-hour neutral salt spray test in the embodiment;
[0028] Figure 8 This is a scanning electron microscope point element map of the surface of the bearing steel workpiece after 96 hours of neutral salt spray test in the example. DETAILED DESCRIPTION
[0029] Specific implementation method 1: The surface treatment method for improving the corrosion resistance of 8Cr4Mo4V steel bearings in this implementation method is implemented according to the following steps:
[0030] 1. Sample surface cleaning:
[0031] The 8Cr4Mo4V steel bearing parts are placed in a cleaning solution for ultrasonic cleaning to remove surface oil and contaminants to obtain cleaned bearing parts;
[0032] 2. Argon ion etching treatment:
[0033] Put the cleaned bearing parts into the workstation in the vacuum chamber and evacuate the vacuum chamber. When the back vacuum is less than 1×10 -3 After the pressure reaches 1-10 Pa, argon working gas is introduced, and the pressure reaches 1-10 Pa. The argon gas is excited by radio frequency to form plasma, and a negative bias voltage is applied to the bearing parts to perform ion bombardment cleaning, thereby obtaining the bearing parts after ion cleaning.
[0034] 3. Initial nitrogen ion implantation:
[0035] In a plasma ion implanter equipped with a magnetron sputtering target, nitrogen is used as the working gas, the working gas pressure in the vacuum chamber is adjusted to 0.1-1 Pa, radio frequency is used to excite nitrogen to form plasma, and the bearing parts after ion cleaning are subjected to nitrogen plasma ion implantation treatment to form a pretreatment layer, thereby obtaining bearing parts subjected to pre-nitrogen ion implantation treatment;
[0036] 4. Magnetron sputtering deposition of chromium layer:
[0037] The working gas pressure in the vacuum chamber is adjusted to 0.1-5 Pa, argon is used as the working gas, argon is excited into plasma by radio frequency, and a chromium layer is deposited on the bearing parts pre-treated by nitrogen ion implantation by magnetron sputtering using a pure chromium target for 0.5-5 hours, and a chromium layer is deposited on the surface of the bearing parts;
[0038] 5. Plasma ion implantation of nitrogen:
[0039] The working gas pressure in the vacuum chamber is adjusted to 0.1-1 Pa again, nitrogen is switched as the working gas, radio frequency is used to excite nitrogen to form plasma, and nitrogen plasma ion implantation is performed on the bearing parts. The acceleration voltage is controlled to 10-50 kV to form a nitrogen-chromium atomic mixed layer on the surface of the bearing parts.
[0040] 6. Cyclic magnetron sputtering deposition of chromium and nitrogen ion implantation:
[0041] Repeat the magnetron sputtering deposition of the chromium layer in step 4 and the nitrogen plasma ion implantation in step 5 for many times to form a nitrogen-chromium atomic mixed layer (of a certain thickness) on the surface of the bearing parts, thereby completing the surface treatment method for improving the corrosion resistance of 8Cr4Mo4V steel bearings.
[0042] The purpose of the cyclic treatment in step six of this embodiment is to increase the thickness of the nitrogen-chromium atomic mixed layer to meet the corrosion resistance requirements of different lifespans.
[0043] This embodiment provides an improved multi-layer coating structure, which achieves efficient ion implantation and stable coating deposition by optimizing process parameters, thereby greatly improving the corrosion resistance and mechanical properties of bearing steel. This process method is widely applicable to surface engineering treatment of aviation, automobile and industrial bearings.
[0044] Specific implementation method 2: The difference between this implementation method and specific implementation method 1 is that in step 1, the bearing steel workpiece is ultrasonically cleaned by anhydrous ethanol.
[0045] Specific implementation method three: The difference between this implementation method and specific implementation method one or two is that the time of ion bombardment cleaning in step two is 1 to 1.5 hours.
[0046] Specific implementation method four: The difference between this implementation method and any one of specific implementation methods one to three is that in step two, RF is used to excite argon to form plasma, the RF power is controlled to be 40-50W, and a negative bias voltage of 200-700V is applied to the bearing parts through a high-voltage pulse power supply, the pulse width is 20-30μs, and the frequency is 1000-10000Hz.
[0047] In this embodiment, the positive electrode of the high-voltage pulse power supply is grounded.
[0048] Specific implementation method five: The difference between this implementation method and any one of specific implementation methods one to four is that in step three, radio frequency is used to excite nitrogen to form plasma, and a negative bias voltage of 20 to 40 kV, a pulse width of 10 to 15 μs, and a frequency of 100 to 300 Hz is applied to the bearing parts through a high-voltage pulse power supply to perform nitrogen ion implantation treatment.
[0049] Specific embodiment 6: The difference between this embodiment and specific embodiments 1 to 5 is that the treatment time of step 3 nitrogen plasma ion implantation is 1 to 1.5 hours.
[0050] Specific implementation seven: This implementation differs from any one of specific implementations one to six in that a magnetron sputtering process is used in step four, a negative bias voltage of 200 to 400 V is applied to the bearing parts by a high-voltage pulse power supply, the pulse width is controlled to be 20 to 30 μs, and the frequency is 1000 to 10000 Hz.
[0051] In this embodiment, the positive electrode of the high-voltage pulse power supply is grounded.
[0052] Specific implementation eight: This implementation differs from specific implementation seven in that in step four, a chromium layer with a thickness of 15 to 50 nm is deposited on the surface of the bearing part.
[0053] Specific embodiment 9: The difference between this embodiment and any one of specific embodiments 1 to 8 is that in step 5, the nitrogen plasma ion implantation treatment time is controlled to be 0.5 to 10 hours.
[0054] Specific embodiment 10: The difference between this embodiment and any one of specific embodiments 1 to 9 is that in step 6, the magnetron sputtering treatment in step 4 and the nitrogen ion implantation into the chromium layer in step 5 are repeated 3 to 20 times.
[0055] Embodiment: The surface treatment method for improving the corrosion resistance of 8Cr4Mo4V steel bearings in this embodiment is implemented according to the following steps:
[0056] 1. Sample surface cleaning:
[0057] Anhydrous ethanol is used to ultrasonically clean a bearing steel workpiece made of 8Cr4Mo4V steel to remove grease and impurities on the surface of the outer ring of the bearing, thereby obtaining a cleaned bearing steel workpiece;
[0058] 2. Argon ion etching treatment:
[0059] Place the cleaned bearing steel workpiece on the sample table in the vacuum chamber and evacuate the vacuum chamber to 10 -4 After 0.04 Pa, argon working gas is introduced, the pressure of the vacuum chamber is adjusted to maintain at 0.1 Pa, argon is excited by radio frequency to form plasma, a bias voltage of 500 V is applied to the workpiece, and the bearing steel workpiece is etched for 1 hour. Argon ions are accelerated to impact the surface of the bearing outer ring, and the impurities attached to the surface are etched to obtain the bearing parts after ion cleaning;
[0060] 3. Initial nitrogen ion implantation:
[0061] The working gas pressure in the vacuum chamber was adjusted to 0.25 Pa, nitrogen was used as the working gas, the nitrogen gas flow rate was 30 sccm, radio frequency was used to excite nitrogen to form plasma, the acceleration voltage was controlled to be 20 kV, the pulse width was 10 μs, and the frequency was 200 Hz. Nitrogen ion implantation was performed under vacuum conditions for 1 h to form a pretreatment layer to improve the bonding strength of the coating, and a bearing part pre-treated by nitrogen ion implantation was obtained;
[0062] 4. Magnetron sputtering deposition of chromium layer:
[0063] The working pressure in the vacuum chamber was adjusted to 2.5 Pa, argon was used as the working gas, the argon gas flow rate was 500 sccm, the negative bias voltage was controlled to be 200 V, the pulse width was 25 μs, the frequency was 10000 Hz, and a cycle was 12 minutes. The target material was pure chromium. The magnetron sputtering process was used to perform magnetron sputtering treatment on the bearing steel workpiece with the transition layer, and a 17 nm chromium layer was deposited on the surface of the bearing steel workpiece;
[0064] 5. Nitrogen ion implantation into chromium layer:
[0065] The working pressure in the vacuum chamber was adjusted to 0.25 Pa again, and nitrogen was used as the working gas, and the gas flow rate of nitrogen was controlled to be 30 sccm. The nitrogen was excited by radio frequency to form plasma, and the nitrogen ions were accelerated by a high-voltage electric field to bombard the surface of the chromium layer with an energy of 20 keV, and the nitrogen ions were implanted into the chromium layer for 30 minutes;
[0066] 6. Cyclic magnetron sputtering deposition of chromium and nitrogen ion implantation:
[0067] Repeat the magnetron sputtering treatment in step 4 and the nitrogen ion implantation chromium layer treatment in step 5 for multiple times to form 8 layers of composite coating. The total thickness of the composite coating is 134 nm and the surface nanohardness is 20.3 GPa, thereby completing the surface treatment method for improving the corrosion resistance of complex-shaped bearings.
[0068] After the surface treated bearing outer ring is evenly coated with 4210 anti-corrosion oil, a 96h neutral salt spray test is carried out in accordance with the national standard GB / T 10125-2021 "Artificial atmosphere corrosion test". The test results are as follows Figure 6 As shown in the figure, the outer ring treated by this process has no rust on the surface after 96 hours of salt spray and is still shiny. For further rigorous observation, the outer ring treated by surface treatment after 96 hours of salt spray test was cut by wire, and the raceway position was microscopically observed and tested. The morphology is shown in the figure. Figure 7 As shown, the surface morphology of the raceway is uniform, restoring the surface gully morphology just after processing. There is no obvious contrast difference at each position. The surface energy spectrum is measured point by point. The results are shown in Figure 8 , six positions were selected in the point measurement mode. There were only five element signals of C, N, Cr, Fe, and O at the six positions, no Cl element signal, and the mass percentage of O element was within 2%. It can be considered that the surface adsorbed oxygen in the atmosphere, indicating that there was no corrosion at the raceway position and the surface condition was good.
Claims
1. A surface treatment method for improving the corrosion resistance of 8Cr4Mo4V steel bearings, characterized in that The surface treatment method for improving the corrosion resistance of 8Cr4Mo4V steel bearings is implemented according to the following steps:
1. Sample surface cleaning: The 8Cr4Mo4V steel bearing parts are placed in a cleaning solution for ultrasonic cleaning to obtain cleaned bearing parts; 2. Argon ion etching treatment: Put the cleaned bearing parts into the workstation in the vacuum chamber and evacuate the vacuum chamber. When the back vacuum is less than 1×10 -3 After the pressure reaches 1-10 Pa, argon working gas is introduced, and the pressure reaches 1-10 Pa. The argon gas is excited by radio frequency to form plasma, and a negative bias voltage is applied to the bearing parts to perform ion bombardment cleaning, thereby obtaining the bearing parts after ion cleaning.
3. Initial nitrogen ion implantation: In a plasma ion implanter equipped with a magnetron sputtering target, nitrogen is used as the working gas, the working gas pressure in the vacuum chamber is adjusted to 0.1-1 Pa, radio frequency is used to excite nitrogen to form plasma, and the bearing parts after ion cleaning are subjected to nitrogen plasma ion implantation treatment to form a pretreatment layer, thereby obtaining bearing parts subjected to pre-nitrogen ion implantation treatment; 4. Magnetron sputtering deposition of chromium layer: The working gas pressure in the vacuum chamber is adjusted to 0.1-5 Pa, argon gas is used as the working gas, and a pure chromium target is used to deposit a chromium layer on the bearing parts pre-treated by nitrogen ion implantation by magnetron sputtering for 0.5-5 hours, so as to deposit a chromium layer on the surface of the bearing parts; 5. Plasma ion implantation of nitrogen: The working gas pressure in the vacuum chamber is adjusted to 0.1-1 Pa again, nitrogen is switched as the working gas, radio frequency is used to excite nitrogen to form plasma, and nitrogen plasma ion implantation is performed on the bearing parts. The acceleration voltage is controlled to 10-50 kV to form a nitrogen-chromium atomic mixed layer on the surface of the bearing parts.
6. Cyclic magnetron sputtering deposition of chromium and nitrogen ion implantation: Repeat the magnetron sputtering deposition of the chromium layer in step 4 and the nitrogen plasma ion implantation in step 5 for many times to form a multi-layer nitrogen-chromium atomic mixed layer on the surface of the bearing parts, thereby completing the surface treatment method for improving the corrosion resistance of 8Cr4Mo4V steel bearings.
2. The surface treatment method for improving the corrosion resistance of 8Cr4Mo4V steel bearing according to claim 1 is characterized in that In step 1, the bearing steel workpiece is ultrasonically cleaned by anhydrous ethanol.
3. The surface treatment method for improving the corrosion resistance of 8Cr4Mo4V steel bearing according to claim 1 is characterized in that The time of ion bombardment cleaning in step 2 is 1 to 1.5 hours.
4. The surface treatment method for improving the corrosion resistance of 8Cr4Mo4V steel bearing according to claim 1, characterized in that In step 2, RF is used to excite argon to form plasma, and the RF power is controlled to be 40-50W. A negative bias voltage of 200-700V is applied to the bearing parts through a high-voltage pulse power supply, with a pulse width of 20-30μs and a frequency of 1000-10000Hz.
5. The surface treatment method for improving the corrosion resistance of 8Cr4Mo4V steel bearing according to claim 1, characterized in that In step three, radio frequency is used to excite nitrogen to form plasma, and a negative bias voltage of 20 to 40 kV, a pulse width of 10 to 15 μs, and a frequency of 100 to 300 Hz is applied to the bearing parts through a high-voltage pulse power supply to perform nitrogen ion implantation treatment.
6. The surface treatment method for improving the corrosion resistance of 8Cr4Mo4V steel bearing according to claim 1, characterized in that The treatment time of step three nitrogen plasma ion implantation is 1 to 1.5 hours.
7. The surface treatment method for improving the corrosion resistance of 8Cr4Mo4V steel bearing according to claim 1, characterized in that In step 4, a magnetron sputtering process is used, and a negative bias voltage of 200 to 400 V is applied to the bearing parts through a high-voltage pulse power supply, and the pulse width is controlled to be 20 to 30 μs and the frequency is 1000 to 10000 Hz.
8. The surface treatment method for improving the corrosion resistance of 8Cr4Mo4V steel bearing according to claim 1, characterized in that In step 4, a chromium layer with a thickness of 15 to 50 nm is deposited on the surface of the bearing part.
9. The surface treatment method for improving the corrosion resistance of 8Cr4Mo4V steel bearing according to claim 1, characterized in that In step five, the nitrogen plasma ion implantation treatment time is controlled to be 0.5 to 10 hours.
10. The surface treatment method for improving the corrosion resistance of 8Cr4Mo4V steel bearing according to claim 1, characterized in that In step six, the magnetron sputtering treatment in step four and the nitrogen ion implantation chromium layer treatment in step five are repeated 3 to 20 times.
Citation Information
Patent Citations
Cr4Mo4V steel bearing carbon-nitrogen plasma radical ion carburizing method by means of warming
CN102134696A
Method for preparing spinel oxide protective coating of stainless steel connector of solid oxide fuel battery
CN105239050A
Special steel surface treatment method
CN111733395A
Preparation method of high-chromium composite nitriding layer with high corrosion resistance on surface of iron-based alloy
CN112210756A
Cited By
Damage-resistant gradient control manufacturing method for bearing area of high-performance rolling bearing
CN121344520A